Analisis Citra Merek, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Kedelai - Aditya, Erin; Laksono, Sonny SM (Otonomi, 2025)
This research aims to determine consumer characteristics, whether consumers at the Sumber Rohmat Soybean Store are more likely to make purchasing decisions based on brand image, product quality or price. This research is quantitative, in which there are 3 independent variables and 1 dependent variable. The population in this study was 210 people in total from all customers at each branch of the Sumber Rohmat soybean shop with a sample of 138 respondents. Data collection in this study used a questionnaire and then processed using the multiple linear regression analysis method. The results of this research show that: 1) Brand image has a significant influence and the hypothesis is accepted with reference to a t value of 1.792 with a significance level of 0.075. (2) Price has a significant influence and the hypothesis is accepted with reference to a t value of 4.526 with a significance level of 0.001. (3) Product quality has a significant influence and the hypothesis is accepted with reference to a t value of 2.483 with a significance level of 0.000. The results of the 3 independent variables that have a significant influence are the price variable, but this does not mean that the other 2 independent variables have no influen Suggestions for this research: Considering that the price variable has a significant influence, stores are advised to maintain a competitive pricing strategy that is in line with the quality of the products offered. Companies are also expected to always control the quality of soybeans to improve product quality. Companies still need to build and strengthen their brand image through improving, for example, customer service.